Investigating the Difficulties Encountered by Students of English Department at Elmergib University Using Assimilation Processes (Elmergib Journal of Human Sciences, 2024)
This study aims at investigating Libyan students of English language performance in the area of assimilation as a feature of connected speech at recognition and production levels in order to understand the difficulties they face, and to investigate instructors' views in the same area in order to limit these difficulties. To demonstrate the changes that occur in connected speech, a descriptive method was used, as well as an interview and test to collect data.According to the findings of this study, the majority of English as a foreign language (EFL) Libyan students at Elmergib University lack the proper knowledge of connecting speech in general. Because of their lack of knowledge during their university studies, most of the participants have difficulty grasping the phenomenon of assimilation, recognizing the regressive and progressive types of the phenomenon, and showing the created sounds. The researchers recommend that educational institutions prioritise the subject by offering intensive programmes and utilizing advanced language laboratories.